BLENDED LEARNING METHOD WITHIN INDONESIAN HIGHER EDUCATION INSTITUTIONS - Zamzami Zainuddin; Cut Muftia Keumala (Jurnal Pendidikan Humaniora, 2018)
Abstract: This article aims to explore the potential development of a Blended learning model in Indonesian higher education institutions. The paper attempts to explain the concept of the Blended learning in terms of theory and practice, based on the literature discussed in several reputable international journals. Initially, this method proposes to improve the deficiencies of a traditional learning model which is lack of technological resources and at the same time to improve the gap of e-learning practice which is lack of a face-to-face learning experience. In the blended instruction, students will learn through a face-to-face interaction in the classroom and supported by learning media such as a Website, Video or Learning Management System (LMS). Meanwhile, the use of technologies is ordinarily used for students’ learning and peers interaction outside of class, especially for online discussion and homework submission. This method emphasizes that learning activity should not only occur in the classroom but also outside of the class through online media.Key Words: blended learning, hybrid learning, learning management systems, e-learning, conventional learningAbstrak: Tuliskan Artikel ini bertujuan untuk menggali potensi pengembangan metode pembelajaran Blended learning pada perguruan tinggi Indonesia. Tulisan mencoba memaparkan konsep pembelajaran Blended learning dari segi teori dan praktik berdasarkan literatur dari beberapa jurnal internasional bereputasi. Lahirnya metode ini bertujuan untuk menyempurnakan kekurangan dari metode pembelajaran konvensional face-to-face yang tidak menggunakan media teknologi dalam pembelajaran, serta kekurangan pada metode pembelajaran e-learning  yang mengesampingkan pembelajaran tatap muka. Dalam metode ini siswa akan belajar secara tatap muka di kelas yang didukung oleh berbagai media pembelajaran seperti website, video, dan Learning Management System (LMS). Dalam praktiknya, penggunaan media teknologi sebenarnya lebih banyak digunakan untuk proses pembelajaran di luar kelas terutama untuk diskusi online dan mengumpulkan tugas. Metode ini menekankan bahwa pembelajaran bukan hanya terjadi di kelas saja secara tatap muka, tetapi juga di luar kelas melalui media online.Kata kunci: blended learning, hybrid learning, learning management systems, e-learning, pembelajaran konvensional